The Controversy Will Continue! Issues Concerning the Conceptualisations and Assessment of Creativity and the Impact it has on Education - Stephen Pritchard (Educational Futures, 2020)
This article will argue the need for a new multidimensional approach to creativity in order to solve ongoing problems concerning the conceptualisations and measurements within the field. First, an overview of the numerous assessments of creativity present in the literature will be provided. Second, the varying roots of creativity and conceptualisations will be presented to demonstrate the disparity within the research. Finally, recommendations will be made in order to approach creativity in a new multidimensional way to attempt to improve the current problematic nature of creativity within the education system.